Evaluation System for Agricultural and Rural Modernization in China - Zhoufu Yan; Lewei Peng; Xiao Wu (Agriculture, 2023)
High-quality development of agricultural and rural areas is the foundation of national modernization and sustainable development in China. Therefore, the evaluation of the degree of development of modernization of China’s agricultural and rural areas and the summarization of its main characteristics are crucial. However, studies on rural modernization and coordinated development are limited. Here, we developed a statistical evaluation system to effectively identify and assess the levels of agricultural and rural modernization, urban–rural integration, and agricultural rural coordination. We found that agricultural and rural modernization in China has continued to improve, but low scores were attributed to the factors of coordinated development of urban–rural areas, livable ecological environment, farmer prosperity, industrial structure upgrade, and resource allocation efficiency, limiting high-quality agricultural and rural development. Agricultural and rural modernization is lower in the central and western regions, compared to that in the eastern regions, but it is picking up the pace, indicating convergence. Rural modernization is lower than agricultural modernization and the two subsystems are not sufficiently coordinated, especially in undeveloped areas. Furthermore, the regional differences in rural modernization are greater than those in agricultural modernization. The system developed here can provide valuable experience for developing countries to open new paths toward modernization.